Hydrochlorothiazide Test as a Tool in the Diagnosis of Gitelman Syndrome in Chinese Patients - Peng, Xiaoyan; Zhao, Bingbin; Zhang, Lei; Jiang, Lanping; Yuan, Tao; Wang, Ying; Wang, Haiyun; Ma, Jie; Li, Naishi; Zheng, Ke; Nie, Min; Li, Xuemei; et al. (Frontiers in Endocrinology, 2018)
Traditional clinical diagnostic criteria for Gitelman syndrome (GS) including hypomagnesemia and hypocalciuria have been challenged by reports of atypical manifestations recently, as well as the development of genetic testing. Hydrochlorothiazide (HCT) test is a diagnostic method different from the traditional biochemical parameters, which could evaluate the function of thiazide-sensitive sodium-chloride co-transporter (NCC) in vivo by a small dose of NCC inhibitor HCT. In this retrospective study, we compared the diagnostic significance of hypomagnesemia, hypocalciuria and the reaction of HCT test, among Chinese patients with GS confirmed by genetic test. For patients who were clinically suspected of GS manifestations, SLC12A3 gene was sequenced to make genetic diagnosis. A total of 83 GS and 19 control patients were recruited, among which 37 underwent HCT test according to the standard process. Compared with the gold standard of genetic diagnosis, both the diagnostic sensitivity (93.10%) and specificity (100.00%) of the HCT test were much higher than those of hypomagnesemia and/or hypocalciuria. The area under the receiver operating characteristic (ROC) curve was 1.000 (95% CI 0.905-1.000) for HCT test, higher than the values using hypomagnesemia and/or hypocalciuria. The cost of HCT test was around $54, much lower than genetic diagnosis. In conclusion, besides traditional hypomagnesemia and hypocalciuria, HCT test could be a valuable tool in the clinical diagnosis of Chinese GS patients.